O tecido fáustico nas Américas: procedimentos tradutórios e repercussões nas culturas - Roque, Isabel Rebelo (2024)
This doctoral dissertation is based on the concept of Faustic tissue, formulated by Jerusa Pires Ferreira, and traces a cartography of the trajectory of the mythical figure of Faust, including its incorporations and translations into the most different languages, especially in literature, theater, music and cinema. We discuss precursors of Faust, such as Cyprian of Antioch, and the mutations of Faust from his historical figure to the consolidation of the myth in his pact with Mephistopheles. We also debate the first narratives, oral and written, going through tragedy, redemption and salvation, up to the insertion of Goethe's Faust in modernity and its incorporations and translations in an incessant process and in new languages. Then, this cartography detects reverberations in the translations of the Faustic in Latin America and North America. To this end, we evoke concepts from Lotman’s cultural semiotics and those of transcreation and transluciferation elaborated by Haroldo de Campos, among others. The objective is to identify and highlight possible cultural and mythical intersections between the Faustic figures of Latin America and North America, in a section highlighted throughout the work, which brings African crossroads myths into dialogue. The methodology is qualitative, with procedures for surveying, selecting, analyzing, comparing and intertwining bibliographic material, including fictional, documentary, literary, cinematographic and musical, always taking into account the specificities of each language. With this set of procedures, Search resources that allow the emergence of differences and points of convergence, as well as the strength of the myth in bringing together the cultures mentioned here